An Empirical Study on the Behavioral Intention of College Students’ Online Ideological and Political Learning - Miaomiao Ren; Yan Ma; Wenxiang Fan; Mingyong Li; Yuming Feng (International Journal of Digital Multimedia Broadcasting)
Based on the integration of the technology acceptance model and the information system success model, this study constructs the structural equation model of college students’ online ideological and political learning behavioral intention; then, a questionnaire survey is conducted among college students from 7 colleges of Chongqing and Hangzhou. The results show that there are group differences in system perception, technology acceptance perception, and behavioral intention among college students with different genders and grades; different dimensions of information system quality have different effects on behavioral intention; perceived ease of use is an important mediating variable, which has a direct positive impact on the use attitude; perceived usefulness and use attitude have positive direct effects on behavioral intention; and perceived usefulness has a higher predictive effect on behavioral intention. Therefore, we put forward four suggestions. First, in the future practice, we should pay attention to the group differences of college students and constantly improve the practice mechanism of network ideological and political education. Second, we propose to take the quality construction of information system as the goal and constantly consolidate the service system of network platform. Third, we believe that we can improve users’ attitude towards the use of the platform by improving their perception of ease of use. Finally, we also suggest that we should focus on improving users’ useful perception of the platform, so as to promote their use behavior.